Some data from the recent outbreaks of newcastle disease in Greece - Παππούς, Χρ.; Μπατιάνης, Ν.; Σεϊμένης, Α.; Καΐλας, Β.; Λίτκε, Ο. (Journal of the Hellenic Veterinary Medical Society, 2019)
Towards the end of December 1983 and the begining of 1984, outbreaks of Newcastle disease appeared in poultry farms of Megara (district of Attica). From the severe epizootic during the years 1969-1973 no outbreaks were verified in the country since then. In some farms the disease appeared in a severe forme with the classic symptoms and high rate of deaths. In other farms the mild form prevailed with varying rate of Infection. The pathogenicity tests of two epizootic virus strains isolated, yielded the following indexes respectively: - Mean death time of the minimal infective dose in chick embryos: 48 and 41.6 hours. - Intracerebral pathogenicity in day-old chicks: 1.35 and 1.45. - Intravenous pathogenicity in 51 day birds: 1.90 and 1.75. The above data in association to the clinical symptoms of the experimental disease in 51 day old birds, i. e. oedema of the head, diarrhoea enteric hemorrhage and death in 3-5 days, could classify both virus strains as velogenic-viscerotropic ones. The HI antibody titers in the vaccinated birds of different ages by the drinking water, eye drop or spray routes are presented